Answer
Step-by-step explanation:
One solution :
x = -1/3 = -0.333
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
-5*(3*x+1)+4*x-(10*x+2)=0
Step by step solution :
Step 1 :
Equation at the end of step 1 :
((0 - 5 • (3x + 1)) + 4x) - (10x + 2) = 0
Step 2 :
Step 3 :
Pulling out like terms :
3.1 Pull out like factors :
-21x - 7 = -7 • (3x + 1)
Equation at the end of step 3 :
-7 • (3x + 1) = 0
Step 4 :
Equations which are never true :
4.1 Solve : -7 = 0
Answer: 1/2 times 6x equals 3x and then you do 1/2 times 4 and that equals 2 then multiply the 3 and 4 in the parenthesis and that is 12 then add 12 to the 3 and 2 and your answer is 17.
Step-by-step explanation:
Answer:
6 more students
Step-by-step explanation:
hope this helps
Answer:
the answer is D because "difference" is a key word for subtraction
Step-by-step explanation:
Answer:
A
Step-by-step explanation:
The y intercept = (0,0) since the c value = 0.
Since the numerical coefficient of x^2 is > 0, the graph opens upward.
a = 1
b = 7
c = 0
The Table describing all the conditions is A